2020
DOI: 10.3389/fimmu.2020.597433
|View full text |Cite
|
Sign up to set email alerts
|

CD71+ Erythroid Cells in Human Neonates Exhibit Immunosuppressive Properties and Compromise Immune Response Against Systemic Infection in Neonatal Mice

Abstract: Newborns are highly susceptible to infectious diseases. The underlying mechanism of neonatal infection susceptibility has generally been related to their under-developed immune system. Nevertheless, this notion has recently been challenged by the discovery of the physiological abundance of immunosuppressive erythroid precursors CD71+erythroid cells (CECs) in newborn mice and human cord blood. Here, as proof of concept, we show that these cells are also abundant in the peripheral blood of human newborns. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 53 publications
2
39
0
Order By: Relevance
“…In contrast to other reports ( Delyea et al., 2018 ; Shahbaz et al., 2018 ), CECs in COVID-19 patients expressed negligible amount of PDL-1/PDL-2 but expressed the V-domain immunoglobulin suppressor of T cell activation ( Figure S1 K). In agreement with our previous reports in other models ( Dunsmore et al., 2017 ; Elahi et al., 2013 ), we found that CECs express significantly higher amounts of arginase II ( Figures 1 F and 1G) and reactive oxygen species (ROS) ( Figures 1 H and 1I) compared with other immune cell lineages, similar to what has been described for their counterparts in human newborns ( Elahi et al., 2020b ), HIV ( Namdar et al, 2019 ), and cancer ( Zhao et al., 2018 ). As a comparison, we measured the expression of ROS in CECs from HIV patients ( Figures S2 A and S2B).…”
Section: Resultssupporting
confidence: 92%
“…In contrast to other reports ( Delyea et al., 2018 ; Shahbaz et al., 2018 ), CECs in COVID-19 patients expressed negligible amount of PDL-1/PDL-2 but expressed the V-domain immunoglobulin suppressor of T cell activation ( Figure S1 K). In agreement with our previous reports in other models ( Dunsmore et al., 2017 ; Elahi et al., 2013 ), we found that CECs express significantly higher amounts of arginase II ( Figures 1 F and 1G) and reactive oxygen species (ROS) ( Figures 1 H and 1I) compared with other immune cell lineages, similar to what has been described for their counterparts in human newborns ( Elahi et al., 2020b ), HIV ( Namdar et al, 2019 ), and cancer ( Zhao et al., 2018 ). As a comparison, we measured the expression of ROS in CECs from HIV patients ( Figures S2 A and S2B).…”
Section: Resultssupporting
confidence: 92%
“…It remains unknown whether EPCs in cancer may induce Treg differentiation, similar to their neonatal counterparts [ 87 ]. Similarly, regardless of a well-established role of EPCs in neonates [ 86 , 94 ], the regulation of myeloid cell response by EPCs in cancer is unknown. Moreover, erythroid cells were reported to produce IL-1β, IL-2, IL-4, IL-6, IFN-γ, and TNF-α [ 306 ]; however, their role in immune regulation by EPCs remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…CECs mediate their immunosuppressive functions via cell–cell interaction and/or soluble mediators such as Arginase I (Arg I), Arginase II (Arg II) and reactive oxygen species (ROS) ( 15 , 17 , 19 22 ). CECs are highly abundant in neonatal mice up to 4-weeks of age regardless of sex and similarly up to 6 months in human newborns ( 18 , 19 , 23 ). Because of the extramedullary erythropoiesis (EE) ( 21 ), CECs expand in the peripheral blood during pregnancy in humans and mice ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%